Pengembangan Gerak Dasar Manipulatif Berbasis Media Inovatif untuk Pembelajaran Penjas SD - Lesmawan, Hendra; Handayani, Widya; Lanos, Muhsana El Cintami; Putri, Siti Ayu Risma; Manullang, Jujur Gunawan; Tarmizi, Machiavelli Herman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to develop an innovative media-based manipulative basic motion learning model in elementary school, with the